Size effect, financial characteristics and insolvency profiles among the SMEs in Malaysia / Maran Marimuthu and Indraah Kolandaisamy - Marimuthu, Maran; Kolandaisamy, Indraah (Universiti Teknologi MARA, Perlis, 2011)
This study makes an attempt to analyze the effect of size on financial characteristics and insolvency of small medium enterprises. The conceptual framework is designed using the right measures, variables, concepts and models. A total sample of 229 businesses is considered consisting of small (57), medium (111) and large (61) SMEs. Non-parametric statistical techniques are used for empirical testing. The results indicate that size effect is significant only on profitability measures. There are no significant differences among the small, medium and large SMEs with regard to insolvency scores. In general, about 55 per cent of the large SMEs fall under the bankruptcy category, as compared to 39 per cent of the small SMEs and about 47 per cent of the medium SMEs. Large SMEs face greater financial risk and thus, face greater insolvency.